Image Encryption and Decryption System Using AES for Secure Transmission - Thakkar, P; Mishra, HK; Shaikh, Z; Sharma, D (International Journal of Computer Sciences and Engineering, 2025)
Internet is the greatest blessing for all the people over the world. Large amount of data is constantly transmitted over the internet. Data means any image, videos, audio etc. Also, confidential information from Banking, Military, Government etc are transmitted over the internet, but the security of these information is not always looked upon. Privacy & Security of information is very important in data storage and transmission. So as to secure the information, various data hiding techniques & encryption of images is done. Image Encryption can be done using various symmetric and asymmetric key algorithms. But, it is found that symmetric key algorithm is much faster and easier to implement and required less processing power as compare to asymmetric key algorithm. Therefore, we use AES Algorithm for the encryption of images. Here, the proposed system mainly deals with the encryption of image using AES algorithm to secure our data during transmission. Different image file formats are given as the input to the AES Algorithm in our system.